Retraction notice to "Volume replacement with hydroxyethyl starch solution in children" [Br J Anaesth 70 (1993) 661–5]. (September 2020) - Boldt, J.; Knothe, C.; Schindler, E.; Hammermann, H.; Dapper, F.; Hempelmann, G.
Abstract : This article has been retracted: please see Elsevier Policy on Article Withdrawal (https://www.elsevier.com/about/our-business/policies/article-withdrawal ). This article has been retracted at the request of the Editor-in-Chief, Professor Hugh Hemmings, based on the recommendations of Justus-Liebig-University Giessen following an internal review of research conducted by Joachim Boldt at the University. This is further described in 'Further Retractions of Articles by Joachim Boldt', https://doi.org/10.1016/j.bja.2020.02.024 .